A new method for non-stationary random critical excitation. - Takewaki, Izuru (Earthquake engineering & structural dynamics.)
Since earthquake ground motions are very uncertain even with the present knowledge, it is desirable to develop a robust structural design method taking into account these uncertainties. Critical excitation approaches are promising and a new non-stationary random critical excitation method is proposed. In contrast to the conventional critical excitation methods, a stochastic response index is treated as the objective function to be maximised. The power (area of power spectral density (PSD) function) and the intensity (magnitude of PSD function) are fixed and the critical excitation is found under these restrictions. It is shown that the original idea for stationary random inputs can be utilized effectively in the procedure for finding a critical excitation for non-stationary random inputs. The key for finding the new non stationary random critical excitation is the exchange of the order of the double maximization procedures with respect to time and to the power spectral density function.